Buerger Allen Exercise Dalam Tatalaksana Gangguan Perfusi Perifer Pada Pasien Diabetes Melitus Tipe II - Hidayatul Rahmi; Willady Rasyid (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2023)
Diabetes Mellitus is a global problem whose prevalence continues to increase from year to year both in Indonesia and the world, this has an impact on social, economic, and patient health. International Diabetes Federation (IDF, 2019) World DM patients in 2013 numbered 382 million and it is estimated that this will double, namely around 592 million sufferers in 2035. Peripheral perfusion disorders are a complication that often occurs in Diabetes Mellitus patients. The risk of peripheral perfusion disorders in diabetes sufferers can be prevented or minimized by using the Burger Allen Exercise. The Buerger Allen exercise has indicators in the form of improvements and increases in ABI (Ankle Brachial Index) values ??which include improving peripheral perfusion. The aim of this community service (PKM) is to provide training and knowledge about the Buerger Allen Exercise as well as provide knowledge on how to care for the feet in an effort to reduce the risk of vascular disorders in DM sufferers. Implementation of the program by providing Buerger Allen Exercise training. Location of PKM activities at Lubuk Buaya Community Health Center, Padang. This activity began with providing health education about Type II Diabetes Mellitus and Buerger Allen Exercise training as well as foot care. This service activity was attended by 11 participants. Patients who attended the activity played an active role during the activity, patients asked questions during the discussion session after the counseling.